EXPERIENCE OF ADMINISTRATION OF GROWTH HORMONE IN TREATMENT OF DIFFERENT TYPES OF MICROSOMIA IN CHILDREN - V.A. Peterkova; E.V. Nagaeva ("Paediatrician" Publishers LLC, 2009)
The opportunities of receiving of genetically engineered medications, e.g. somatotropic hormone (STG) are almost unrestricted, and treatment and monitoring of patients with different types of microsomia can be held on modern, new level with the help of it. STG provides normal stature and valuable quality of life in these patients. Treatment with growth hormone influences on hormonal, metabolic and psychical status of patient. Metabolic effects are: increasing of muscle strength, improving of renal blood flow, increasing of cardiac output, absorbability of calcium in intestines and mineralization of bones. The level of blood cholesterol, lipoproteins is descended; blood alkaline phosphatase, phosphorus, urine and fatty acid are increased. Patients' vitality and quality of life are normalized. Besides somatotropic insufficiency, growth hormone is widely used in growth_stimulating treatment of different types of dwarism in children: microsomia due to pre_natal growth delay, genetic syndromes: Silwer-Russell, Shereshevsky-Turner, Nunan, Prader-Willi, and microsomia in patients with chronic renal disease. Key words: children, microsomia, somatotropic hormone, treatment. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(2):86-93)